1993
DOI: 10.1128/aac.37.5.1108
|View full text |Cite
|
Sign up to set email alerts
|

Iron-dependent free radical generation from the antimalarial agent artemisinin (qinghaosu)

Abstract: Artemisinin is an important new antimalarial agent containing a bridged endoperoxide. The in vitro antimalarial activity of an artemisinin derivative, arteether, is antagonized by two iron chelators, pyridoxal benzoylhydrazone and 1,2-dimethyl-3-hydroxypyrid-4-one. Similarly, the acute toxicity of artemisinin in mice is antagonized by another chelator, deferoxamine-hydroxyethylstarch. A combination of artemisinin and hemin oxidizes erythrocyte membrane thiols in vitro, and this oxidation is also inhibited by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
176
1
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(192 citation statements)
references
References 40 publications
(41 reference statements)
11
176
1
4
Order By: Relevance
“…This cleavage of the peroxide is mediated by iron, which makes iron a necessity in the early onset of artemisinin action [32,33]. In fact, the oxidizing effects of artemisinin on parasitic membranes are greatly enhanced in the presence of haem [34], and haem itself is known to react with artemisinin [9,22,35].…”
Section: Discussionmentioning
confidence: 99%
“…This cleavage of the peroxide is mediated by iron, which makes iron a necessity in the early onset of artemisinin action [32,33]. In fact, the oxidizing effects of artemisinin on parasitic membranes are greatly enhanced in the presence of haem [34], and haem itself is known to react with artemisinin [9,22,35].…”
Section: Discussionmentioning
confidence: 99%
“…Formation of carbon-centered free radicals has been suggested. 5,[8][9][10][11][12] A recent meta-analysis revealed that ART-containing regimens substantially reduce treatment failure compared to standard antimalarial treatments. 13 ART can significantly prolong the time span of antimalarial treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to artemisinin and malaria, it is believed that 2 sequential steps ate involved. Activation of artemisinin inside the malarial parasite by heme or other iron systems results in cleavage of endoperoxide bridges and generation of free radicals, and formation of covalent complexes between these free radicals and malaria-specific proteins or specific receptors (MESHNICK et al, 1991(MESHNICK et al, , 1993ZHANG et al, 1992;KAMCHONW~NGPAISAN & MESHNICK, 1996;MESHNICK, 1998;DHINGRA et al, 2000). Both the parent artemisinin compound and its more active derivative artemether (HIEN & WHITE, 1993) are rapidly metabolized to the biologically active dihvdroartemisinin WHITE.…”
Section: Discussionmentioning
confidence: 99%